Impact Of Patient Wheel-On Time on Emergency Department Efficiency and Patient Outcomes - Ghildiyal, Neha; Sharma, Tarun; Chauhan, Garima; Ranawat, Abhishek; Paliyal, Sanchi; Sanjeet, Sanjeet; Samikhya, Soumya (Journal of Neonatal Surgery, 2025)
Emergency Departments (EDs) worldwide face persistent challenges such as overcrowding, prolonged wait times, and resource constraints, which negatively impact patient outcomes. One critical but underexplored factor affecting ED efficiency is Patient Wheel-On Time, defined as the interval from a patient’s arrival to their placement in a treatment area.. This paper looks at how Wheel-On Time affects general emergency care efficiency, patient outcomes, and hospital throughput. A review of all the current studies shows that delays in Wheel-On Time help to explain longer lengths of stay (LOS), higher rates of being left without being seen (LWBS), and worse clinical results, especially in time-sensitive diseases like sepsis and stroke. The paper offers a mixed-methods study technique that includes both quantitative analysis of hospital data and qualitative views from healthcare staff and patients in order to find out how lowering Wheel-On Time affects the success of treatment, the happiness of patients, and the efficiency of ED process. The results should help lawmakers and hospital managers improve the performance of the ED by using ideas like pre-hospital bed assignments, extra staffing models, and technology driven screening systems.